2000
DOI: 10.1007/s002130000418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recent and reference antipsychotic agents at human dopamine D 2 and D 3 receptor signaling in Chinese hamster ovary cells

Abstract: Olanzapine and sertindole were less efficacious dopamine antagonists in intact cell assays, possibly due to avid uptake in cells. For sertindole, the weak hD2S receptor antagonism in intact cells corresponded to a weak in vivo central dopamine antagonism assessed in rats. However, for olanzapine, hD2S receptor binding affinity correlated better with its in vivo dopamine antagonist potency. Such discrepancies may be further explained by relative differences of the compounds in penetrating into the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Activation of hD 3 receptors by DA led to enhanced [ 35 S]GTP␥S binding Vanhauwe et al, 2000), an effect potently and reversibly blocked by S33138, indicating competitive antagonist properties. Moreover, using an SPA procedure coupled to a highly selective antibody (Millan et al, 2004a;Neve et al, 2004), the activation of G␣ i3 by DA was also shown to be antagonized by S33138.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Activation of hD 3 receptors by DA led to enhanced [ 35 S]GTP␥S binding Vanhauwe et al, 2000), an effect potently and reversibly blocked by S33138, indicating competitive antagonist properties. Moreover, using an SPA procedure coupled to a highly selective antibody (Millan et al, 2004a;Neve et al, 2004), the activation of G␣ i3 by DA was also shown to be antagonized by S33138.…”
Section: Discussionmentioning
confidence: 97%
“…The higher affinity of S33138 for hD 3 versus hD 2L and hD 2S receptors distinguishes it from haloperidol, clozapine, olanzapine, risperidone, and other clinically available antipsychotics displaying similar affinities for hD 3 , hD 2L , and hD 2S sites (Table 2) (Millan et al, 2000a;Vanhauwe et al, 2000;Burstein et al, 2005). Furthermore, the marked D 3 versus D 2 receptor preference of S33138 likewise differentiates it from aripiprazole and bifeprunox, which behave as partial agonists at hD 3 and hD 2 receptors (Shapiro et al, 2003;Burstein et al, 2005;Novi et al, 2007;Urban et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanhauwe et al (2000) had reported that these compounds should be considered as D 2 receptor antagonists based on their inhibition of AC, although melperone was not studied by them. We hypothesized that a study of their regulation of D 2L function might reveal functional characteristics that explained some of their behavioral atypicality.…”
Section: Discussionmentioning
confidence: 99%